2023
DOI: 10.9734/ajahr/2023/v10i1217
|View full text |Cite
|
Sign up to set email alerts
|

Alternate Bearing in Fruit Crops: Causes and Control Measures

Abstract: Alternate bearing (AB) is a phenomenon, common in fruit crops, is a concerned plant or branch or orchard does not bear a regular crop year-after-year rather heavy yields are followed by extremely light yield and vice versa. Based on the alternate bearing index, it is divided in four groups viz.,  no alternation, less alternate, high alternate, severe alternate. There are mainly two factors are responsible for alternate bearing i.e., exogenous and endogenous factors. Alternate bearing can be managed by cultural… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 39 publications
0
4
0
Order By: Relevance
“…However, the fruit buds dropped during kernel development during the "ON" years. It has been reported that excessive fruit-bud abscission in pistachio started in June, at the time of embryo development, and increased during July, causing the next year to be the "OFF year" [1,2,6,19].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, the fruit buds dropped during kernel development during the "ON" years. It has been reported that excessive fruit-bud abscission in pistachio started in June, at the time of embryo development, and increased during July, causing the next year to be the "OFF year" [1,2,6,19].…”
Section: Discussionmentioning
confidence: 99%
“…Essentially, it involves a cycle of high fruit set (ON) in one year and low fruit set (OFF) in the subsequent year. This pattern leads to excessive fruit set in ON years, leading to non-bearing or smaller fruits in the following year [2]. Fluctuation between ON and OFF years poses financial challenges for producers and consumers and causes significant losses in fruit tree crops.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The fact that eleven successive olive harvests were conducted in this study, using a total of 30 trees, provided insights into the alternate bearing of olive trees that deserve commentary. Alternate bearing in fruit trees is characterized by a good harvest invariably followed by a poor one, and vice versa, known as "On" and "Off" years, respectively [31,32]. Attempts to explain this alternation have focused on hormonal effects exerted by developing seeds in the current year on the floral induction of buds that would bloom in the following year, with the involvement of gibberellins [33], auxins [31], or phenols [34] suggested.…”
Section: The Alternate Bearing Habit Of Olivementioning
confidence: 99%